Digitally assisted, fully integrated, wideband transmitters for high-speed millimeter-wave wireless communication links. ([2019]) - Del Rio, David; Rezola, Ainhoa; Sevillano, Juan F; Velez, Igone; Berenguer, Roc
No abstract available